Ptolemais of the Hunts : a Ptolemaic settlement in the Indian Ocean (3rd century BCE - 1st century CE) - (:unkn) unknown (My University, 2019)
Alexander the Great's expedition to Asia was accompanied by the founding of many settlements. This policy was continued by the king's successors in their respective kingdoms. However, King Ptolemy II, who possessed Egypt, distinguished himself from all his rivals by founding a city on the African shore of the Red Sea. This settlement, named Ptolemaïs of the Hunts, was the first step in a vast project which aimed to hunt African elephants and train them for war. This article aims to assess and discuss what we know about this urban foundation, which marks an important historical moment. Indeed, for the first time Europe set foot the Indian Ocean area durably. Some points which have been not much examined so far are addressed in this article.
Keywords: African Research